(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Young people need counseling and guidance to be able to discoverabilities, inclinations and to outline their future. Career guidance andcounseling should be made permanent from primary and secondary education. Witha permanent reformed educational system that does not value counseling andvocational guidance of scholars, Indian educational system has a major minus.But the insufficiency of counselors in the school education, determines thehigh rate of disorientation of the potential students in choosing the facultythat they want to graduate from, or worse, determines school dropout. The present investigationwas directed towards the identification of counseling needs of the secondaryschool students as perceived by secondary school teachers by normative surveymethod. For this, a Counseling Needs inventory was constructed by theinvestigator. Results of the analysis indicate that secondary school studentshave strong counseling needs, as perceived by their teachers. Results also showthat there is no significant difference between male and female teacherperception on the counseling needs of secondary school students.